Salvage of cardiopulmonary collapse caused by ethanol sclerotherapy for vascular malformations: clinical experience at a single center and literature review - Su, Lixin; Zhao, Yan; Shen, Yuchen; Fan, Xindong; Wang, Zhenfeng; Wang, Deming; Li, Qingyang (Frontiers in Cardiovascular Medicine, 2024)
ObjectiveThis review aims to summarize the salvage experience of cardiopulmonary collapse occurring as a result of absolute ethanol sclerotherapy for vascular malformations.MethodsIn total, we reviewed three cases of cardiopulmonary collapse induced by ethanol sclerotherapy for vascular malformations and described the details of the salvage procedure. Saturation of pulse oxygen (SpO2), end-tidal CO2, and invasive arterial pressure were the routine monitors for ethanol injection patients. Cardiopulmonary resuscitation, epinephrine, norepinephrine, and deoxyepinephrine were mainly used to correct circulation parameters. Manually ventilated via endotracheal intubation with 100% O2, increased respiratory rate were mainly used to correct Respiratory parameters.ResultsAll three cases were successfully salvaged without major complications. When cardiopulmonary collapse occurred, manual ventilation via endotracheal intubation with 100% O2, increased ventilation frequency and external cardiac compression were the emergency treatments. Epinephrine, norepinephrine, deoxyepinephrine infusion solely or combined were crucial to maintaining the basic vital signs.ConclusionDespite the severity of cardiopulmonary collapse caused by ethanol sclerotherapy, it can be detected by close observation and reversed with timely treatment.